Preparation and Characterization of Iron Oxide Decorated Graphene Nanoplatelets for Use as Barrier Enhancing Fillers in Polyurethane Based Solar Cell Encapsulant. (2020) - Yuwawech, Kitti; Wootthikanokkhan, Jatuphorn; Tanpichai, Supachok
Abstract: This work has concerned the development of iron oxide (Fe3 O 4 )/graphene nanoplatelets (GNPs) for use as barrier enhancing filler in polyurethane based encapsulating materials. The aim of this work is to investigate the effects of GNPs types and the concentration of Fe3 O4 on orientation the functionalized GNPs in the PU composites under magnetic field. It was hypothesized that, by properly controlling the orientation of GNPs in the polymer matrix, the greater barrier properties of the composite encapsulant can be expected. Experimentally, Fe3 O4 nanoparticles were firstly prepared by treating ferric chloride hexahydrate (FeCl3 .6H2 O) with hydrazine (N2 H4 ). After that, the product (Fe3 O4 ) was introduced into GNPs. The ratio of the Fe3 O4 nanoparticles to GNPs was varied between 0.1 and 1. Superparamagnetic behavior of the composite was observed when the weight ratio of Fe3 O 4 to GNPs was greater than 0.3/1. Consequently, this ratio was used for the preparation of polyurethane/GNPs nanocomposite. Finally, the feasibility of applying the film reinforced with PU/Fe3 O4 decorated GNPs as an encapsulating material for a flexible organic photovoltaic cell was explored. Performance and durability of the various devices were measured and compared.